Network News - Quebec Community Groups Network (QCGN) (2024)

Innovative Mentorship Program Equips English-Speaking Quebecers With Workplace French Skills - Provincial Employment Roundtable (PERT) (2024)

Un programme novateur de mentorat pour renforcer les compétences en français des Québécois d'expression anglaise en milieu de travail - Provincial Employment Roundtable (PERT) (2024)

PERT’s Recommendations Included in New Report on the Economic Development of Offi cial Language Minority Communities - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

QCGN Pleased by Federal Support for Minority Economic-Development Plan - Quebec Community Groups Network (QCGN) (2024)

QFHSA Board of Directors Disappointed by Vacancies in 2024 School Board Elections - Quebec Federation of Home and School Associations (QFHSA) (2024)

English-speaking Quebec Plays Vital Role in Boosting French, Language Commissioner Says - Quebec Community Groups Network (QCGN) (2024)

Selon le commissaire aux langues officielles, le Québec d’expression anglaise joue un rôle essentiel dans la promotion du français - Quebec Community Groups Network (QCGN) (2024)

The ESCC Newsletter : October 2024 - English Speaking Catholic Council (2024)

Network News - Quebec Community Groups Network (QCGN) (2024)

New Language Directives in Health a Welcome, Significant Step, QCGN Says - Quebec Community Groups Network (QCGN) (2024)

Selon le QCGN, les nouvelles directives linguistiques dans le domaine de la santé sont une étape importante et positive - Quebec Community Groups Network (QCGN) (2024)

Le QCGN se dit heureux de l’adoption de la motion visant à supprimer le certificat d’identité permettant d’avoir accès aux soins de santé - Quebec Community Groups Network (QCGN) (2024)

QCGN Pleased by Motion To Nix Identity Certificate for Health Care - Quebec Community Groups Network (QCGN) (2024)

Health Directives Should Be Scrapped, Not Tweaked, QCGN Says - Quebec Community Groups Network (QCGN) (2024)

Les directives sur la santé devraient être abandonnées et non ajustées, selon le QCGN - Quebec Community Groups Network (QCGN) (2024)

Déclaration concernant la rencontre avec le ministre Roberge - Quebec Community Groups Network (QCGN) (2024)

QCGN Invites Ministers Dubé, Roberge and Girard to Meeting on Directives - Quebec Community Groups Network (QCGN) (2024)

The ESCC Newsletter : August 2024 - English Speaking Catholic Council (2024)

OQLF Has No Business in Quebec Operating Rooms, QCGN Says - Quebec Community Groups Network (QCGN) (2024)

Selon le QCGN, l'OQLF n'a rien à faire dans les salles d'opération du Québec - Quebec Community Groups Network (QCGN) (2024)

Participation à la conférence de l’ACFAS sur les femmes officielles des communautés linguistiques minoritaires à Ottawa - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

Building Bridges Between Communities Valuable, QCGN Annual Meeting Is Told - Quebec Community Groups Network (QCGN) (2024)

L’importance de bâtir des ponts entre les communautés : Un sujet à l’ordre du jour de l’assemblée annuelle du QCGN - Quebec Community Groups Network (QCGN) (2024)

Busting Myths : Report Shows English-speaking Quebecers Are Key Part of a National-Unity Solution - Quebec Community Groups Network (QCGN) (2024)

Détruire les mythes : Un rapport démontre que les Québécois d'expression anglaise sont un élément clé d'une solution pour l'unité nationale - Quebec Community Groups Network (QCGN) (2024)

Attending the ACFAS Official Women Minority Language Communities Conference in Ottawa - Provincial Employment Roundtable (PERT) (2024)
Keywords: Official Language Minority Community (OLMC)

Report Card on French May Bring More Coercive Measures, QCGN Says - Quebec Community Groups Network (QCGN) (2024)

Selon le QCGN, les notes en français dans le bulletin scolaire risquent d’entraîner d’autres mesures coercitives - Quebec Community Groups Network (QCGN) (2024)

English Parents' Committee Association Newsletter - English Parents' Committee Association (EPCA) (2024)

The ESCC Newsletter : April 2024 - English Speaking Catholic Council (2024)

QCGN Sees Some Good News for English-speaking Quebecers in 2024–2025 Budget - Quebec Community Groups Network (QCGN) (2024)

Selon le QCGN, le budget 2024-2025 apporte de bonnes nouvelles aux Québécois d’expression anglaise - Quebec Community Groups Network (QCGN) (2024)

Network News - Quebec Community Groups Network (QCGN) (2024)

Le QCGN profondément déçu par la décision de la Cour d'appel qui confirme la constitutionnalité de la Loi sur la laïcité de l’État - Quebec Community Groups Network (QCGN) (2024)

QCGN Profoundly Disappointed by Quebec Court of Appeal’s Ruling on Bill 21 - Quebec Community Groups Network (QCGN) (2024)

English Parents' Committee Association Newsletter - English Parents' Committee Association (EPCA) (2024)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2024)

Network News - Quebec Community Groups Network (QCGN) (2024)

Communauté du CHSSN Netlink - Community Health and Social Services Network (CHSSN) (2024)

Community Netlink - Community Health and Social Services Network (CHSSN) (2024)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2024)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2024)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2024)

Network News - Quebec Community Groups Network (QCGN) (2023)
Keywords: Official Language Minority Community (OLMC)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2023)

Déclaration du QCGN sur le rapport du Bloc Québécois concernant le financement fédéral de la minorité d’expression anglaise du Québec - Quebec Community Groups Network (QCGN) (2023)

QCGN Statement on Bloc Québécois report on federal funding for Quebec’s English-speaking minority - Quebec Community Groups Network (QCGN) (2023)

Lancement d’une pétition pour la révision de la réforme radicale du réseau de la santé prévue par le projet de loi 15 - Quebec Community Groups Network (QCGN) (2023)

Petition demands rethink of Bill 15’s radical revamp of Health Care Network - Quebec Community Groups Network (QCGN) (2023)

Avoiding the News Desert : Addressing Challenges Around Community Media in English-speaking Quebec : Research Brief no. 10 - Bell, Shannon (Quebec English-speaking Communities Research Network (QUESCREN), 2023)

Éviter le désert mediatique : Relever les défis des médias régionaux dans le Québec anglophone : Résumé de recherche no. 10 - Bell, Shannon (Quebec English-speaking Communities Research Network (QUESCREN), 2023)

English Parents' Committee Association Newsletter - English Parents' Committee Association (EPCA) (2023)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2023)

Network News - Quebec Community Groups Network (QCGN) (2023)

Seniors Action Quebec E-Newsletter - Seniors Action Quebec (SAQ) (2023)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2023)

The QFHSA Board of Directors Unanimously Supports the Bill 40 Judgment - Quebec Federation of Home and School Associations (QFHSA) (2023)

Network News - Quebec Community Groups Network (QCGN) (2023)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

Apprendre le français à l’âge adulte : examen des pratiques exemplaires actuelles en francisation des adultes au Québec - Provincial Employment Roundtable (PERT) (2023)
L’apprentissage du français représente un défi pour beaucoup de minorités linguistiques au Québec. Vu la primauté grandissante du français dans la province, l’apprentissage de cette langue est une priorité de plus en plus importante pour les personnes qui sont confrontées à des obstacles liés au français et qui souhaitent participer au marché du travail et à la société québécoise dans son ensemble. La Table ronde provinciale sur l’emploi (PERT) s’est déjà penchée sur l’écosystème québécois de la francisation des adultes pour se faire une idée de la disponibilité et de l’accessibilité des programmes offerts dans la province. Nos constats : le cadre québécois de francisation des adultes est une mosaïque de programmes à la disponibilité et aux coûts variables, et d’importants obstacles se dressent devant les personnes apprenantes selon leur lieu de vie, leur statut migratoire et leur statut d’emploi, entre autres critères d’admissibilité.

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

Network News - Quebec Community Groups Network (QCGN) (2023)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2023)

[Newsletter] - Youth for Youth Québec (Y4Y Québec) (2023)

English Parents' Committee Association Newsletter - English Parents' Committee Association (EPCA) (2023)

[Newsletter] - Youth for Youth Québec (Y4Y Québec) (2023)

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

Network News - Quebec Community Groups Network (QCGN) (2023)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2023)

[Newsletter] - Youth for Youth Québec (Y4Y Québec) (2023)

House of Commons Committee Votes to Forsake English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2023)

Un comité de la Chambre des communes vote pour l’abandon des Québécoises et des Québécois d’expression anglaise - Quebec Community Groups Network (QCGN) (2023)

English Parents' Committee Association Newsletter - English Parents' Committee Association (EPCA) (2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2023)

Le budget du Québec doit s'attaquer au sous-financement de nos groupes communautaires : QCGN - Quebec Community Groups Network (QCGN) (2023)

Quebec Budget Must Address Underfunding of Our Community Groups : QCGN - Quebec Community Groups Network (QCGN) (2023)

English Parents' Committee Association Newsletter - English Parents' Committee Association (EPCA) (2023)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2023)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2023)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2023)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2023)

Community NetLink - Community Health and Social Services Network (CHSSN) (2023)

Literacy Quebec Newsletter : Special Edition - Literacy Quebec (LQ) (2023)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2023)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2023)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2023)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2023)

Annual Report 2022-2023 - Seniors Action Quebec (SAQ) (2023)

Rapport annuel 2022-2023 - Seniors Action Quebec (SAQ) (2023)

Working Together Pays Dividends for Official Language Minority Communities! - Quebec English-language Production Council; Quebec Community Groups Network (QCGN); English Language Arts Network (ELAN); Alliance nationale de l'industrie musicale; Alliance des producteurs francophones du Canada (APFC); Fédération culturelle canadienne-française (FCCF) (2022)

Seniors Action Quebec Announces Change to Board of Directors - Seniors Action Quebec (SAQ) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Legislative Update, Bill C-13 An Act to Amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Businesses Act and to Make Related Amendments to Other Acts - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

E-Newsletter - Seniors Action Quebec (SAQ) (2022)

Press Release : Seniors Action Quebec Announces Appointment of New Executive Director - Seniors Action Quebec (SAQ) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Le QCGN félicite Éric Girard, nouveau ministre responsable des Relations avec les Québécois d’expression anglaise - Quebec Community Groups Network (QCGN) (2022)

QCGN Congratulates Eric Girard, New Minister Responsible for Relations with English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

Le QCGN demande la nomination d’un ministre responsable des Relations avec les Québécois d’expression anglaise - Quebec Community Groups Network (QCGN) (2022)

English Parents' Committee Association Newsletter - English Parents' Committee Association (EPCA) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

Literacy Quebec Newsletter - Literacy Quebec (LQ) (2022)

English Parents' Committee Association Newsletter - English Parents' Committee Association (EPCA) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

E-Newsletter - Seniors Action Quebec (SAQ) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

English Parents' Committee Association Newsletter - English Parents' Committee Association (EPCA) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

QFHSA News Bulletin : Statement on the Coalition Avenir Quebec's Refusal to Budge on Provisions for English-speaking CEGEP Students - Quebec Federation of Home and School Associations (QFHSA) (2022)

The Advisor - Assistance and Referral Centre (ARC) (2022)

Activity Report : A Year In Review 2021-22 - Literacy Quebec (LQ) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

CHSSN Community Netlink - Community Health and Social Services Network (CHSSN) (2022)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2022)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2022)

Community NetLink - Community Health and Social Services Network (CHSSN) (2022)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2022)

Annual Report 2021-2022 - Youth for Youth Québec (Y4Y Québec) (2022)

Network News - Quebec Community Groups Network (QCGN) (2021)

E-Newsletter - Seniors Action Quebec (SAQ) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Press Release : Seniors Action Quebec Announces Change in Executive Leadership - Seniors Action Quebec (SAQ) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Press Release : A Celebration in Song, Spoken Word & Step Final Episode of We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Making Homemade Tomato Sauce with Greg on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Quebec Online Alliance (QOA) - the Online Campus for Students with Medical Exemptions from the English School Boards Across Quebec Officially Opened this Week - Leading English Education and Resource Network (LEARN) (2021)

English Parents' Committee Association Newsletter - English Parents' Committee Association (EPCA) (2021)

Network News - Quebec Community Groups Network (QCGN) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Press Release : Author Conversations with Richard King on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Organic Gardening with Hannah on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

English Parents' Committee Association Newsletter - English Parents' Committee Association (EPCA) (2021)

E-Newsletter - Seniors Action Quebec (SAQ) (2021)

2020-21 Annual Report - Voice of English-speaking Quebec (VEQ) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Press Release : Urban Art with Jamie on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Tango Dancing with Mireille & Friends on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Network News - Quebec Community Groups Network (QCGN) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Press Release : Making Jam with Susan on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : The Flamboyant World of Drag with Barbada on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Community Organization of Lanaudière (ECOL) (2021)

Network News - Quebec Community Groups Network (QCGN) (2021)

E-Newsletter - Seniors Action Quebec (SAQ) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Press Release : Wine Pairing with Ana on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Horse Therapy with Karine on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Home and School : Advocating for Education : Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2021)

Press Release : Indigenous Hoop Dancing with Makhena on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

English Parents' Committee Association Newsletter - English Parents' Committee Association (EPCA) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Press Release : Bird Watching with Joël Coutu on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Eating Healthy on a Budget with Crystal on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

English Parents' Committee Association Newsletter - English Parents' Committee Association (EPCA) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Press Release : Animal Fostering with Cindy on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Spring Special! Gardening in Small Spaces on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

English Parents' Committee Association Newsletter - English Parents' Committee Association (EPCA) (2021)

Network News - Quebec Community Groups Network (QCGN) (2021)

Press Release : Flower Arranging on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Laughter Yoga on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

English Parents' Committee Association Newsletter - English Parents' Committee Association (EPCA) (2021)

E-Newsletter - Seniors Action Quebec (SAQ) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Press Release : New Episode of Web Series for Seniors We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : New York Times Bestselling Author Louise Penny Is The Guest of the Web Series for Seniors We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

English Parents' Committee Association Newsletter - English Parents' Committee Association (EPCA) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

QFHSA News Bulletin - Quebec Federation of Home and School Associations (QFHSA) (2021)

Press Release : Celebrated New York Times Bestselling Author Louise Penny, on Senior’s Web Series We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2021)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2021)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2021)

Community NetLink - Community Health and Social Services Network (CHSSN) (2021)

Community NetLink - Community Health and Social Services Network (CHSSN) (2021)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2021)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2021)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2021)

Annual Report 2020-2021 - Youth for Youth Québec (Y4Y Québec) (2021)

Press Release : A Holiday Concert of Quebec Performers at Martha Wainwright's URSA Follows Incredibly Popular First Episode of "We're All In This Together" - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2020)

Network News - Quebec Community Groups Network (QCGN) (2020)

Press Release : Launch of Project We Are All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2020)

E-Newsletter - Seniors Action Quebec (SAQ) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Newsletter - Seniors Action Quebec (SAQ) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

EPCA Lauds New Monies, Lifitng of Bureaucratic Controls : Disappointed in Lack of Option for Parents - English Parents' Committee Association (EPCA) (2020)

Back to School Plan : Working Together for a Serene and Safe Return to School - English Parents' Committee Association (EPCA); Quebec Federation of Parents’ Committees (FCPQ) (2020)

Plan pour la rentrée scolaire : Travailler ensemble pour une rentrée sereine et sécuritaire - English Parents' Committee Association (EPCA); Quebec Federation of Parents’ Committees (FCPQ) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

September Return to School : Parents Must Be Involved in Process - English Parents' Committee Association (EPCA) (2020)

Network News - Quebec Community Groups Network (QCGN) (2020)

Newsletter - Seniors Action Quebec (SAQ) (2020)

2019-20 Annual Report - Voice of English-speaking Quebec (VEQ) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Seniors Action Quebec Statement on Situation at Residence Herron - Seniors Action Quebec (SAQ) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Network News - Quebec Community Groups Network (QCGN) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2020)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2020)

Community NetLink - Community Health and Social Services Network (CHSSN) (2020)
Keywords: Official Language Minority Community (OLMC)

Community NetLink - Community Health and Social Services Network (CHSSN) (2020)

Enhancing Regional Capacity / Reforcer la capitacité communautaire régionale - Community Health and Social Services Network (CHSSN) (2020)

Pledge to Parent Governance - English Parents' Committee Association (EPCA) (2020)

Applauding Parents on Councils and Service Centre Boards - English Parents' Committee Association (EPCA); Quebec Federation of Parents’ Committees (FCPQ) (2020)

Annual Report 2020 - Youth for Youth Québec (Y4Y Québec) (2020)

Network News - Quebec Community Groups Network (QCGN) (2019)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2019)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2019)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2019)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2019)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2019)

English-speaking fathers in Quebec exposed to greater vulnerability - Community Health and Social Services Network (CHSSN) (2019)

English-speaking Fathers in Quebec Exposed to Greater Vulnerability - Community Health and Social Services Network (CHSSN) (2019)

Network News - Quebec Community Groups Network (QCGN) (2019)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2019)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2019)

Network News - Quebec Community Groups Network (QCGN) (2019)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2019)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2019)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2019)

Community NetLink - Community Health and Social Services Network (CHSSN) (2019)

Community NetLink - Community Health and Social Services Network (CHSSN) (2019)

Enhancing Regional Capacity / Reforcer la capitacité communautaire régionale - Community Health and Social Services Network (CHSSN) (2019)

Annual Report 2018-2019 - Youth for Youth Québec (Y4Y Québec) (2019)

QCGN Mourns Loss of James Shea, Educator and Advocate for Linguistic Duality - Quebec Community Groups Network (QCGN) (2018)

Network News - Quebec Community Groups Network (QCGN) (2018)

Network News - Quebec Community Groups Network (QCGN) (2018)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2018)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2018)

Network News - Quebec Community Groups Network (QCGN) (2018)

Network News - Quebec Community Groups Network (QCGN) (2018)

Network News - Quebec Community Groups Network (QCGN) (2018)

CHSSN Community Netlink - Community Health and Social Services Network (CHSSN) (2018)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2018)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2018)

Community NetLink - Community Health and Social Services Network (CHSSN) (2018)

Network News - Quebec Community Groups Network (QCGN) (2017)

Network News - Quebec Community Groups Network (QCGN) (2017)

QCGN Mourns the Loss of Gretta Chambers, une Grande Dame of Quebec - Quebec Community Groups Network (QCGN) (2017)

Community NetLink - Community Health and Social Services Network (CHSSN) (2017)

Community NetLink - Community Health and Social Services Network (CHSSN) (2017)

Network News - Quebec Community Groups Network (QCGN) (2016)

Network News - Quebec Community Groups Network (QCGN) (2016)

Network News - Quebec Community Groups Network (QCGN) (2016)

Network News - Quebec Community Groups Network (QCGN) (2016)

QCGN Mourns the Loss of Community Advocate, Dr. Victor Goldbloom - Quebec Community Groups Network (QCGN) (2016)

Community NetLink - Community Health and Social Services Network (CHSSN) (2016)

Community NetLink - Community Health and Social Services Network (CHSSN) (2016)

ELAN to be Represented on Matv Advisory Committee - English Language Arts Network (ELAN) (2015)

Guy Rodgers Named Compagnon (Champion) of the Ordre des arts et des lettres du Québec - English Language Arts Network (ELAN) (2015)

ELAN Board of Directors Update : Peter MacGibbon Moves on, Bettina Forget Welcomed as Interim President - English Language Arts Network (ELAN) (2015)

Community NetLink - Community Health and Social Services Network (CHSSN) (2015)

Community NetLink - Community Health and Social Services Network (CHSSN) (2014)

Community NetLink - Community Health and Social Services Network (CHSSN) (2014)

ELAN's Guy Rodgers Elected for Another Term on Culture Montréal Board - English Language Arts Network (ELAN) (2013)

Community NetLink - Community Health and Social Services Network (CHSSN) (2013)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2013)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2013)

Info-liens / Info-link : CHSSN’s info-links for researchers interested in addressing the topic of improving the health and well-being of English-speaking minority communities in Québec - Community Health and Social Services Network (CHSSN) (2012)
Keywords: Official Language Minority Community (OLMC)

Declaration from the Community Priority Setting Conference of the English-Speaking Community of Quebec - Quebec Community Groups Network (QCGN) (2012)

Q Write - Quebec Writers' Federation (QWF) (2012)

Community NetLink - Community Health and Social Services Network (CHSSN) (2012)

Community NetLink - Community Health and Social Services Network (CHSSN) (2012)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2012)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2012)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2012)

Q Write - Quebec Writers' Federation (QWF) (2012)

Q Write - Quebec Writers' Federation (QWF) (2012)

Q Write - Quebec Writers' Federation (QWF) (2011)

Q Write - Quebec Writers' Federation (QWF) (2011)

Info-liens / Info-links : Info-liens du RCSSS-CHSSN avec les chercheurs et chercheuses ayant un intérêt pour l’amélioration de la santé et le bien-être des communautés d’expression anglaise vivant en situation minoritaire au Québec - Community Health and Social Services Network (CHSSN) (2011)
Keywords: Official Language Minority Community (OLMC)

Community NetLink - Community Health and Social Services Network (CHSSN) (2011)

Community NetLink - Community Health and Social Services Network (CHSSN) (2011)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2011)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2011)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2011)

Q Write - Quebec Writers' Federation (QWF) (2011)

Q Write - Quebec Writers' Federation (QWF) (2011)

November 2010 : Anniversary Newspaper - Literacy Volunteers of Quebec (2010)

Q Write - Quebec Writers' Federation (QWF) (2010)

Q Write - Quebec Writers' Federation (QWF) (2010)

ELAN Launches Recognizing Artists : Enfin Visibles! - English Language Arts Network (ELAN) (2010)

Q Write - Quebec Writers' Federation (QWF) (2010)

Q Write - Quebec Writers' Federation (2010)

Community NetLink - Community Health and Social Services Network (CHSSN) (2010)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2010)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2010)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2010)

Community NetLink - Community Health and Social Services Network (CHSSN) (2009)

Community NetLink - Community Health and Social Services Network (CHSSN) (2009)

Community NetLink - Community Health and Social Services Network (CHSSN) (2009)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2009)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2009)

Community NetLink - Community Health and Social Services Network (CHSSN) (2008)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2008)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2008)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2008)

English-language Arts Organization to Launch New Education Initiatives - English Language Arts Network (ELAN) (2007)

Community NetLink - Community Health and Social Services Network (CHSSN) (2007)

Community NetLink - Community Health and Social Services Network (CHSSN) (2007)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2007)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2007)

QAAL Newsletter - Quebec Association for Adult Learning (QAAL) (2007)

QAAL Newsletter - Quebec Association for Adult Learning (QAAL) (2007)

E-Newsletter - Quebec Association for Adult Learning (QAAL) (2006)

E-Newsletter - Quebec Association for Adult Learning (QAAL) (2006)

E-Newsletter - Quebec Association for Adult Learning (QAAL) (2006)

Community NetLink - Community Health and Social Services Network (CHSSN) (2006)

Community NetLink - Community Health and Social Services Network (CHSSN) (2006)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2006)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2006)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2006)

Community NetLink - Community Health and Social Services Network (CHSSN) (2005)

Community NetLink - Community Health and Social Services Network (CHSSN) (2005)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2005)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2005)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2005)

QCGN News - Quebec Community Groups Network (QCGN) (2005)

QCGN President's Report 2003-2004 - Murphy, Martin P. (Quebec Community Groups Network (QCGN), 2004)
The Quebec Community Groups Network (QCGN) has been in existence on a formal basis since 1995. Much has been accomplished in these past nine years. Looking to the future, there are many challenges which require our attention, strong leadership and innovative ideas to enrich our identity and resolve. It is imperative that the QCGN conrinue to buiid its credibility as a strong and unhesitating voice of reason in working to enhance the development of the English-speaking minority population in Quebec.

Community NetLink - Community Health and Social Services Network (CHSSN) (2004)

The GOAL Post - Guidance-Oriented Approach to Learning (GOAL) Networking Committee (2004)

President's Report on Highlights of Activities Representing QCGN : June 2002 - June 2003 - Murphy, Martin P. (Quebec Community Groups Network (QCGN), 2003)

Community NetLink - Community Health and Social Services Network (CHSSN) (2003)

Community NetLink - Community Health and Social Services Network (CHSSN) (2003)

Alliance Quebec Board of Directors Elect an Interim President - Alliance Quebec (AQ) (2001)

Alliance Quebec Board of Directors Will Elect an Interim President - Alliance Quebec (AQ) (2001)

The Alliance Report - Alliance Quebec (AQ) (1988)

The Alliance Report - Alliance Quebec (AQ) (1987)

The Alliance Report - Alliance Quebec (AQ) (1987)

The Monthly Report - Alliance Quebec (AQ) (1986)

The Monthly Report - Alliance Quebec (AQ) (1986)

The Quebecer - Alliance Quebec (AQ) (1986)

The Quebecer - Alliance Quebec (AQ) (1986)

The Monthly Report - Alliance Quebec (AQ) (1985)

The Monthly Report - Alliance Quebec (AQ) (1985)

The Monthly Report - Alliance Quebec (AQ) (1985)

The Monthly Report - Alliance Quebec (AQ) (1985)

The Monthly Report - Alliance Quebec (AQ) (1985)

The Monthly Report - Alliance Quebec (AQ) (1985)

The Quebecer - Alliance Quebec (AQ) (1985)

The Monthly Report - Alliance Quebec (AQ) (1984)

The Monthly Report - Alliance Quebec (AQ) (1984)

The Monthly Report - Alliance Quebec (AQ) (1984)

The Monthly Report - Alliance Quebec (AQ) (1984)

The Monthly Report - Alliance Quebec (AQ) (1984)

The Monthly Report - Alliance Quebec (AQ) (1984)

The Monthly Report - Alliance Quebec (AQ) (1984)

The Quebecer - Alliance Quebec (AQ) (1983)

The Monthly Report - Alliance Quebec (AQ) (1983)

The Quebecer - Alliance Quebec (AQ) (1983)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1966)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1966)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1966)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1966)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1966)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1965)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1965)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1965)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1965)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1965)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1965)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1964)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1964)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1964)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1964)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1964)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1964)

Quebec Home & School News - Quebec Federation of Protestant Home & School Associations (1963)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1959)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1959)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1959)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1959)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1959)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1959)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1958)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1958)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1958)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1958)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1958)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1958)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1957)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1957)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1957)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1957)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1957)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1956)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1956)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1956)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1956)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1955)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1955)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1955)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1955)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1955)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1955)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1955)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1954)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1954)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1954)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1954)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1954)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1954)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1954)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1953)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1953)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1953)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1953)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1953)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1953)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1953)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1953)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1952)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1952)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1952)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1952)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1952)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1952)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1952)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1952)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1951)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1951)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1951)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1951)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1951)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1951)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1951)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1950)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1950)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1950)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1950)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1950)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1950)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1950)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1950)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1949)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1949)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1949)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1949)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1949)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1949)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1949)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1949)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1948)

Quebec Home and School - Quebec Federation of Home and School Associations (QFHSA) (1948)